Residual rectal mucosa after stapled vs. handsewn ileal J-pouch-anal anastomosis in patients with familial adenomatous polyposis coli (FAP) - a critical issue - Ganschow, Petra; Treiber, Irmgard; Hinz, Ulf; Leowardi-Bauer, Christine; Büchler, Markus W.; Kadmon, Martina (Langenbeck's archives of surgery, 2015)
Restorative proctocolectomy has become the standard surgical procedure for familial adenomatous polyposis (FAP) patients. The use of stapler devices has initiated a controversial discussion concerning the ileal pouch-anal reconstruction. Some authors advocate a handsewn anastomosis after transanal mucosectomy. A double-stapled anastomosis leads to better functional results but seems to bear a higher risk of residual rectal mucosa with dysplasia and adenomas. The present study systematically analyses the rate of residual rectal mucosa after restorative proctocolectomy and handsewn vs. stapled anastomosis.
Gesehen am 06.08.2021